Clinical Features and Management of Patients Admitted for Emergency Surgery at Tertiary Care Hospital during COVID-19 Pandemic - Piya, Roshan; Shrestha, Anil; Shrestha, Gentle Sunder (Nepal Journal of Multidisciplinary Research, 2022)
Nobel coronavirus disease 2019 (COVID-19) is an infectious disease and impact on health service was vast. Most of the health services, hospitals and clinics were providing emergency services only. The aim of this study was to assess sign and symptoms and surgical emergency management performed in Department of Surgery and Department of Obstetrics and Gynecology in a tertiary care hospital. A retrospective descriptive study was conducted among suspected and proven COVID- 19 patients admitted in Patan Academy of Health Sciences, Lalitpur. Clinical data of all patients admitted for emergency conditions extracted from the medical records were included in the study. A total of 130 patients admitted for surgery were selected by using convenient sampling method. Mean age of the patients was 29.56±8.87 years. Most of the patients (72.3%) had visited Obstetrics and Gynecology department and 21.5% in Surgery department during the study periods. Among 130 patients 84 (64.6%) had to undergo emergency and elective Lower Segment Caesarean Section (LSCS) and spinal anesthesia was administered for83.1% of the cases. Appendectomy was performed in 15 (11.5%) patients. During COVID-19 pandemic, surgical procedures were limited to urgent surgical service. Most common emergency surgeries were LSCS, Appendicitis and surgical emergency management was lower segment caesarean section and appendectomy.